2019
DOI: 10.1186/s10194-019-0999-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orofacial complete Freund’s adjuvant treatment on the expression of migraine-related molecules

Abstract: Background: Migraine is a neurovascular primary headache disorder, which causes significant socioeconomic problems worldwide. The pathomechanism of disease is enigmatic, but activation of the trigeminovascular system (TS) appears to be essential during the attack. Migraine research of recent years has focused on neuropeptides, such as calcitonin generelated peptide (CGRP) and pituitary adenylate cyclase-activating polypeptide 1-38 (PACAP1-38) as potential pathogenic factors and possible therapeutic offensives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…The current study draws attention to the limited time interval for therapies targeting glutamatergic pathways as well, as based on our previous experiments, a clear shift to dominantly peptide-mediated pain processing can be seen even from 24 h after CFA application [9]. This time point corresponds to the onset of peripheral and central sensitization of the TS as well in this model [10,11,14].…”
Section: Tryptophan Metabolism and Painmentioning
confidence: 64%
See 4 more Smart Citations
“…The current study draws attention to the limited time interval for therapies targeting glutamatergic pathways as well, as based on our previous experiments, a clear shift to dominantly peptide-mediated pain processing can be seen even from 24 h after CFA application [9]. This time point corresponds to the onset of peripheral and central sensitization of the TS as well in this model [10,11,14].…”
Section: Tryptophan Metabolism and Painmentioning
confidence: 64%
“…1). Similar to the previous experiment on PACAP and CGRP in the same model [9], only sham-injected rats processed 24 h following the injection were used as CO, as a pilot study conducted on naïve and shaminjected (processed 24 and 48 h following injection) rats demonstrated that there is no difference in the level of the metabolites of interest, in neither TNC, nor ssCX (n = 3 in each group, data not shown). The rats were anesthetized with intraperitoneal 4% chloral hydrate solution mainly based on its safe application (CAS ID: 302-17-0, Sigma-Aldrich, St. Louis, MO, USA; 10 ml/kg body weight dose) in the morning and 50 μl of CFA was injected into the right whisker pad.…”
Section: Animal Experiments and Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations